Think about the unthinkable: coastal comprehensive planning for better public outcomes after storm disasters - Snow, Bridget (Kansas State University, 2023)
The last 20 years have contributed to 4 of the top five most active hurricane seasons in the United States, three of them back-to-back. With these stronger storms comes more loss of life, injury to residents and responders, and more destruction of communities. Hurricanes are the most expensive natural disaster that the United States experiences. A single hurricane pass through a city in just a few hours, and still cost more in damages in that single day than a long-term wildfire that takes months to put out. The heightening levels of destruction, and the increasing frequency of large-scale hurricanes are leading many Americans to wonder if it is still safe to live along these coastal areas that are most frequently hit. Many different groups are working to address the need for better long-range planning before hurricanes. These groups are working together to create better solutions for evacuation, protection, and recovery, while working to address the root issues that individual cities face that make them each uniquely vulnerable to hurricanes, especially particular elements like storm surges and long-term flooding. My objective was to provide planners with a framework to study different cities and their response to major storm disasters, and to analyze the different responses to determine best practices when planning for storms. In this report, I explored how two major U.S. coastal cities responded to storms, and which plans were most effective in protecting people for future storm events. A literature review explored frameworks from the Environmental Protection Agency that shaped my study. This provided the base framework for my analysis by identifying the focus areas of built environment, natural environment, society, governance, and risk. My methodology was a combined approach of case study and comparative analysis. I began by identifying major cities that had experienced hurricanes in the 21st century and selected two for case study. I then completed a comparative analysis of the city’s response to their two different storms, and then to each other. Throughout this process, I identified areas of strength and weakness in the responses, as well as areas of change and improvement in between the storms.
Keywords: City planning; Hurricanes; Storm disaster; Emergency preparedness; Storm mitigation